2021
DOI: 10.1093/eurheartj/ehab724.3276
|View full text |Cite
|
Sign up to set email alerts
|

The impact of daily troponin-I and D-dimer serum levels on mortality of moderate-to-severe COVID-19 pneumonia patients

Abstract: Introduction Coronavirus Disease 2019 (COVID-19) caused by that infection resulted in a very high morbidity and mortality rates globally. Purpose The aim of this study is to analyses the daily Troponin-I and D-dimer levels and their impact on the need for intensive care and mortality of the COVID-19 infected patients. Methods 206 patients who were hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although previous observational studies have reported several other inflammatory or coagulation-related makers for the prediction of prognostic outcomes in patients contracting COVID-19 [ 49 , 50 ], our meta-analysis is the first to investigate the association of the F/A ratio with poor prognosis. A previous meta-analysis involving more than two thousand patients revealed significantly higher CRP levels among those who succumbed to COVID-19 than in survivors [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous observational studies have reported several other inflammatory or coagulation-related makers for the prediction of prognostic outcomes in patients contracting COVID-19 [ 49 , 50 ], our meta-analysis is the first to investigate the association of the F/A ratio with poor prognosis. A previous meta-analysis involving more than two thousand patients revealed significantly higher CRP levels among those who succumbed to COVID-19 than in survivors [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another even larger meta-analysis on over 13,000 participants recruited in 77 observational studies has demonstrated a role of the circulating level of cytokines (i.e., IL-6) in predicting severity and mortality in those diagnosed with COVID-19 [ 7 ], further underscoring a detrimental prognostic role of inflammation. In respect to the coagulation–inflammation cascade, previous observational studies have identified D-dimer and fibrinogen as poor prognostic indicators in those contracting COVID-19 [ 25 , 49 , 52 ]. Among these parameters, receiver operating characteristic (ROC) curve analysis in a previous observational study showed the superior accuracy of the F/A ratio (area under curve (AUC) = 0.808) in predicting disease severity and mortality compared with other parameters (i.e., C-reactive protein: AUC = 0.735; fibrinogen: AUC = 0.606; albumin: AUC = 0.257) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study population we included had different severities of illness, and the overall mortality rate was 19%. Many studies have used various biomarkers, such as CRP [ 39 44 ], PCT [ 39 , 43 , 45 , 46 ], IL-6 [ 39 , 43 , 46 ], WBC [ 40 , 47 49 ], D-dimer [ 42 , 44 , 46 , 50 , 51 ], lactate dehydrogenase (LDH) [ 39 , 42 44 , 46 , 47 ], N-terminal pro-B-type natriuretic peptide (NT-proBNP) [ 39 , 52 , 53 ], and Troponin T [ 39 , 54 ], and critical illness scores, such as APACHE II [ 55 57 ], SOFA [ 55 , 56 , 58 60 ], SAPS [ 61 64 ], and CURB65 [ 59 , 61 , 65 ], to evaluate the prognosis of patients with COVID-19. The APACHE II and SOFA scoring systems require the worst values of the clinical and biological parameters to be recorded within 24 h of admission [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study population we included had different severities of illness, and the overall mortality rate was 19%. Many studies have used various biomarkers, such as CRP [39][40][41][42][43][44], PCT [39,43,45,46], IL-6 [39,43,46], WBC [40,[47][48][49], D-dimer [42,44,46,50,51], lactate dehydrogenase (LDH) [39,[42][43][44]46,47], N-terminal pro-B-type natriuretic peptide (NT-proBNP) [39,52,53], and Troponin T [39,54], and critical illness score, such as APACHEII [55][56][57], SOFA [55,56,[58][59][60], SAPS [61-64], and CURB65 [59,61,65], to evaluate the prognosis of patients with COVID-19. The APACHE II and SOFA scoring systems require the worst values of the clinical and biological parameters to be recorded within 24 h of admission [66].…”
Section: Discussionmentioning
confidence: 99%